IGRT/ART phantom with programmable independent rib cage and tumor motion. Issue 2 (28th January 2014) - Haas, Olivier C. L.; Mills, John A.; Land, Imke; Mulholl, Pete; Menary, Paul; Crichton, Robert; Wilson, Adrian; Sage, John; Anna, Morenc; Depuydt, Tom
Abstract : Purpose: : This paper describes the design and experimental evaluation of the Methods and Advanced Equipment for Simulation and Treatment in Radiation Oncology (MAESTRO) thorax phantom, a new anthropomorphic moving ribcage combined with a 3D tumor positioning system to move target inserts within static lungs. Methods: : The new rib cage design is described and its motion is evaluated using Vicon Nexus, a commercial 3D motion tracking system. CT studies at inhale and exhale position are used to study the effect of rib motion and tissue equivalence. Results: : The 3D target positioning system and the rib cage have millimetre accuracy. Each axis of motion can reproduce given trajectories from files or individually programmed sinusoidal motion in terms of amplitude, period, and phase shift. The maximum rib motion ranges from 7 to 20 mm SI and from 0.3 to 3.7 mm AP with LR motion less than 1 mm. The repeatability between cycles is within 0.16 mm root mean square error. The agreement between CT electron and mass density for skin, ribcage, spine hard and inner bone as well as cartilage is within 3%. Conclusions: : The MAESTRO phantom is a useful research tool that produces programmable 3D rib motions which can be synchronized with 3D internal target motion. The easily accessible static lungs enable the use of a wide range of inserts or can be filled with lung tissue equivalent and deformed using the target motion system.